Strategy Based on Computer-Supported Collaborative Learning to Form Workgroups Automatically in an Introductory Programming Course (CS1) - Llanos-Mosquera, Jose-Miguel; Hidalgo-Suarez, Carlos-Giovanny; Bucheli-Guerrero, Victor-Andrés (Revista Facultad de Ingeniería, 2021)
Students of the Introduction to Programming courses present low grades and this is reflected by the high failure and academic desertion rates. In this sense, looking for ways to improve and support the student's academic performance in the Fundamentals of Object-Oriented Programming (FPOO) course, a strategy based on Computer-Supported Collaborative Learning (CSCL) is proposed. It is supported by an algorithm to form workgroups automatically, which allows motivating students and creates a uniform criterion to develop programming tasks. Under the framework of the quasi-experimental design, the strategy was implemented in different evaluative activities of the FPOO course, which allowed us to answer questions related to the improvement of a student's final grade using the automatic formation of workgroups versus the traditional formation of workgroups. Moreover, we compared the grades obtained when activities are developed with no group formation. The experiments in this paper show that using the collaborative strategy improves students' grades by 22% in the laboratories and by 20% in the final project. In addition, it allows the exchange of knowledge to solve a programming task. This paper concludes that developing strategies that integrate collaboration positively impacts the programming learning process and improves student grades and people skills significantly, which encourage a better learning in programming courses.